Pengaruh Pola Asuh Demokratis Terhadap Pemenuhan Gizi Melalui Pemberian Bekal Makanan Anak Usia Dini Kelompok B Usia 5-6 Tahun - Melinda Karim; Irvin Novita Arifin; Yenti Juniarti (PEDAGOGIKA, 2023)
This study aims to determine the influence of democratic parenting styles on nutrition fulfillment through lunch box provision for early childhood Group B aged 5-6 years. This Expost Facto research was conducted on a population of 40 children, with a sample of 17 children. Data were collected through observation and questionnaires. Based on the data analysis result, the value